1975
DOI: 10.1161/01.res.36.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma catecholamine concentrations and vas deferens norepinephrine biosynthesis in men with elevated blood pressure.

Abstract: Systemic biochemical indexes of sympathetic nerve functionplasma catecholamine concentrations and serum dopamine-beta-hydroxylase activitywere correlated with regional indexesnorepinephrine concentration activities of norepinephrine biosynthetic enzymes in the vas deferensānd with blood pressures and pulse rates of 57 men at the time of vasectomy. Mean plasma catecholamine content was increased 66% and 60% in men with elevated systolic and elevated systolic and diastolic blood pressures, respectively. The nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 27 publications
2
5
1
Order By: Relevance
“…If plasma NE levels increase significantly with age only in normotensive subjects, 9 then ultimately NE levels could be expected to be higher in normotensive subjects in extreme old age. Contrary to findings in young and middle-aged hypertensive persons, in whom plasma catecholamine levels are positively related to arterial blood pressure, 57 an inverse relation between plasma NE level and both systolic and diastolic blood pressure has been recently noted in older hypertensive persons. 58 This inverse correlation was confirmed in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…If plasma NE levels increase significantly with age only in normotensive subjects, 9 then ultimately NE levels could be expected to be higher in normotensive subjects in extreme old age. Contrary to findings in young and middle-aged hypertensive persons, in whom plasma catecholamine levels are positively related to arterial blood pressure, 57 an inverse relation between plasma NE level and both systolic and diastolic blood pressure has been recently noted in older hypertensive persons. 58 This inverse correlation was confirmed in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Elevated TH activity in vas deferens of SHR after establishment of hypertension is in agreement with the results in studies on humans by DeQuattro et al (13) who found in creased TH activity in the vas deferens with a concomitant elevated systolic blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…With Bob Mendez 13 we found that plasma CA and tissue levels of NA were both raised and CA biosynthesis activity was increased. The rate limiting step, tyrosine hydroxylase activity, was also increased.…”
Section: Human Vas Deferensmentioning
confidence: 93%